I was just wondering about the steps that are described here but not shown. I don't see what they mean by subtracting equation 3 from equation 1 and using that in equation 2. Could someone show me the steps that were left out?
I was just wondering about the steps that are described here but not shown. I don't see what they mean by subtracting equation 3 from equation 1 and using that in equation 2. Could someone show me the steps that were left out?
Hello,
$\displaystyle \begin{aligned} (1) ~ & 1 &=& {\color{red}\boxed{A}} &+&3B&&& \\
(2) ~ &1&=&&&-B&+&3C \\
(3) ~ &-2&=&{\color{red}\boxed{A}}&&&-&C \end{aligned}$
The red boxes tell us to substract (1) from (3) or (3) from (1).
This gives $\displaystyle 1-(-2)=A+3B-(A-C) \implies 3=3B+C \implies C=3-3B$
Substitute it in (2).